Predicting Conditional Quantiles via Reduction to Classification - Langford, John; Oliveira, Roberto; Zadrozny, Bianca (Twenty-Second Conference on Uncertainty in Artificial Intelligence, 2012)
We show how to reduce the process of predicting general order statistics (and the median in particular) to solving classification. The accompanying theoretical statement shows that the regret of the classifier bounds the regret of the quantile regression under a quantile loss. We also test this reduction empirically against existing quantile regression methods on large real-world datasets and discover that it provides state-of-the-art performance.